Drivers of Growth for Food-Processing SMEs in Cambodia: A Literature Synthesis and Integrated Economic Model - Sam Ean Lay; Mardy SEREY; Sophat Phon (Universitas Muhammadiyah Kotabumi, 2026)
Cambodia's food-processing SMEs occupy a position of considerable strategic consequence within the country's industrial trajectory, yet they remain surprisingly undertheorized in the scholarly literature. The structural imbalance is difficult to overlook: domestic processors transform less than a tenth of total agricultural output, while processed commodities contribute only around 8% of national export earnings — a discrepancy that points to systemic institutional and infrastructural deficiencies rather than mere productive limitations. This chapter assembles a cross-disciplinary body of scholarship — drawing from SME growth theory, agrifood value-chain upgrading, dynamic capabilities, transaction-cost economics, financial constraint theory, food-safety governance, and sustainable transformation — to develop a theoretically grounded account of growth determinants in this sector. The developed framework operates as an analytical diagnostic and policy instrument and is deliberately placed upstream of formal econometric modelling. There is no single driver of growth in this area but the interconnected interplay of firm capabilities, coordination structures, infrastructure, regulatory incentives, and climate-adaptive sourcing. The five-tier upgrading typology gives the argument its punch, pin-pointing the main bottlenecks at each growth stage for the firm. The chapter ends with a simple point: meaningful industrialization will never come from scattered, one-off policy fixes — instead, governments and institutions will need to construct a connected, well-functioning support system that addresses structural barriers together — not one at a time.